Publication productivity of Allied Health Professions in an Italian Local Health Authority: prevalence and bibliometric analysis: Publication productivity of AHPs in Italy - Paci, Matteo; Mazzini, Lisa; Vezzosi, Stefania; Margheri, Mauro; Moretti, Sandra (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: Despite Allied Health Professions (AHPs) represent a substantial part of workforce within the health system and they might give a relevant contribution to research, literature on publication productivity of AHPs working in non-research/academic institutions is scarce. The aim of this investigation was to provide point prevalence of AHPs working in a non- research/academic setting who have written at least one article published in indexed journals, in order to describe their scientific productivity. Methods: A descriptive cross-sectional study was carried out of AHPs working in large Local Health Authority in Italy, who published in journals indexed in Scopus and/or PubMed. H-index, publications and citations number, journal name, publication year, and journal Impact Factor were extracted. Results: Fifty-two AHP workers were identified as authors, having published 105 articles between 1993 and 2019. The number of papers increased over the years (p < .001). Published papers in journals with Impact Factor were 67.6% (n = 71) of the total, with a median Impact Factor = 2.676 (range = 0.583 – 59.102). The median number of citations was 4 (range = 0 – 99). The prevalence among units ranged from 0.8% to 5.0%, 2.9% in the whole department. There were not significant differences in number of articles (p = .138), citations received (p = .337), and H-Index (p = .661) among units. Conclusions: In the Local Health Authority under investigation, publication productivity of AHPs workers was found to be low, although it is increasing over time, with no significant differences among units. Further investigations should be carried out to link these results with authors’ information and organizational characteristics to study the relationship between authors’ profiles and publication productivity.